What Explains the Stock Market's Reaction to Federal Reserve Policy? - BERNANKE, BEN S.; KUTTNER, KENNETH N. (Journal of Finance, 2005)
ABSTRACT This paper analyzes the impact of changes in monetary policy on equity prices, with the objectives of both measuring the average reaction of the stock market and understanding the economic sources of that reaction. We find that, on average, a hypothetical unanticipated 25‐basis‐point cut in the Federal funds rate target is associated with about a 1% increase in broad stock indexes. Adapting a methodology due to Campbell and Ammer, we find that the effects of unanticipated monetary policy actions on expected excess returns account for the largest part of the response of stock prices.